(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rusdaryanti AF, Amalia U, Suharto S. 2020. Antibacterial activity of CaO from blood cockle shells (Anadara granosa) calcination against Escherichia coli. Biodiversitas 21: 2826-2830. Calcium carbonate (CaCO3) in blood clamp shells (BCS) was able to be converted into calcium oxide (CaO) through a calcination process. Some research stated that CaO can be used in the food industries b, one of which is as an antibacterial agent. The purpose of this study was to determine the most optimal size of BCS’s powder during calcination as an antibacterial agent and its effect on the activity of Escherichia coli. Data were analyzed using analysis of variance and Kruskal-Wallis test. The results showed that 200 mesh size of BCS’s powder produced the highest yield of CaO at about 98.68% compared to 120 and 230 mesh size. The best concentration of CaO powder as an antibacterial was 3.5% with a pH of 11.3 ± 0.17. CaO powder had antibacterial activity against E. coli with minimum inhibitory concentration’s value (MIC) of-0.115; a minimum bactericidal concentration’s value (MBC) of 0 CFU/mL; inhibition zone of 3.23 ± 0.2 mm. By the PCR method, DNA degradation has occurred in E. coli cells. The differences of CaO powder concentration had significant effect (P <0.05) on the inhibition zone of E. coli.